Formation Of Ecological Culture Through The Integration Of Ecological Knowledge In Education Of The Natural Geographical Regions Of Kirqulkum And Karaqum - Jobborov Azamjon Mashrabovich; Tojiboyeva Makhliyo Azamjon’s Qizi; Meliyev Muzaffar Saidakbarovich (Global Scientific Publishing, 2023)
This article examines the crucial role of integrating environmental knowledge in the educational system of Kyzylkum and Karakum natural geographical districts. Research focused on building an environmental culture examines the impact of incorporating environmental awareness into curricula. The article aims to shed light on how such integration contributes to the development of a sustainable ecological culture in these unique natural areas through a comprehensive study of educational practices and their impact.
Keywords: Ecological culture; ecological education